Fruit and seedling diversity among sweet chestnut (Castanea sativa Mill.) populations in Turkey - Atar, Fahrettin (Array, 2018)
Sweet chestnut, Castanea sativa Mill., is an important multipurpose tree species in Asia Minor and Europe. The objective of this study was to investigate variation among eight sweet chestnut populations in Turkey by using different morphological characteristics of fruits and seedlings. A total of four fruit characteristics were analysed: fruit length, width and thickness, and fruit shape, i.e. the ratio of fruit length and width. Additionally, 1000 fruit mass and fruit moisture content were determined as well. Measurements of seedling length, root collar diameter and sturdiness quotient were carried out at one-year old seedlings. The highest values of fruit length, width and thickness were found in İzmir population, while the highest values of seedling length, root collar diameter and sturdiness quotient were found in Balıkesir population. The 1000 fruit mass ranged between 3815.1 g and 10516.5 g, and the highest average fruit moisture content was 52.21 %. In general, the fruit size increased from eastern to western populations. Furthermore, the results of statistical analyses showed that there were significant differences between analysed populations for measured morphological characteristics related to both fruit and seedling. Application of cluster analysis revealed grouping of populations according to the eco-geographic principle. However, human influence on the population structure cannot be excluded as well.